Analisis Penggunaan Ejaan dan Bentuk Kata Berdasarkan EYD Edisi V pada Novel Cantik Itu Luka Karya Eka Kurniawan - Melika Debiyana Putri; Alfarizi Wijaya Situmorang; Yunanda Rizki Sitompul; Arion Pardede; Yohana Kartika Marbun (Jurnal Pendidikan dan Kebudayaan (JURDIKBUD), 2026)
This research is motivated by the critical importance of applying standardized Indonesian language rules in literary works to maintain national linguistic integrity amidst the increasingly dynamic evolution of contemporary writing styles. The primary objective of this study is to comprehensively analyze the use of spelling and word forms based on the latest guidelines of the Enhanced Indonesian Spelling System (EYD Edition V) in the novel Cantik Itu Luka by Eka Kurniawan. This novel was selected as the material object due to its status as a masterpiece of modern Indonesian literature, characterized by narrative complexity and a significant sociocultural impact that extends to an international level. The study employs a qualitative descriptive method to factually and accurately describe linguistic phenomena. The research data consist of textual units, including words, phrases, and sentences extracted from the novel's manuscript through documentation, reading, and note-taking techniques. The findings reveal various forms of spelling inconsistencies that deviate from the standard EYD V rules, particularly in the use of punctuation such as commas and colons within complex sentences, the capitalization of national and ethnic names in character dialogues, and the inconsistent italicization of foreign loanwords. From a morphological perspective, the study identifies a highly productive use of affixation (prefixes, suffixes, and confixes) and reduplication. These word formation processes are found to serve not only as grammatical elements but also as the author's stylistic strategy to enliven characters and strengthen emotional intensity within a colonial historical setting. Although some spelling deviations can be categorized as poetic license (licentia poetica), this research emphasizes that EYD V standardization remains crucial as a parameter for structural accuracy in written communication. The implications of this research are expected to contribute to the development of linguistic teaching materials and enhance linguistic sensitivity within the Indonesian literary publishing industry to ensure the continued quality of national literature.